(untitled) (The Pakistan Development Review, 1992)
Ever since its birth as a new discipline, development economics has experienced the heights of universal acclaim as a pioneer (ready to slay the dragon of poverty single-handed) as well as the depths of a heretic isolation (as an outsider to the realm of mainstream economics). Between these two views a consensus is emerging that there is a role, though a reduced one, for development economics. This role exists because the concern for growth and distribution, though in the very veins of mainstream economics, has been highlighted fully only by development economics. However, it is a somewhat reduced role because a greater recognition of the (marginal) utility of free markets, in place of an overly interventionist state - which requires it to speak the language of neo-classical economics, makes it difficult for it to differentiate its ’products’ from those offered by others. There also appears to be a changing perception about the key variable(s) that development economics should focus on: the ends of development (i.e., improving the welfare of the people) rather than the means of achieving it (i.e., the growth of per capita income); a more comprehensive indicator of development composed of such components as longevity and literacy, rather than just per capita income; human capital rather than just physical capital to account for the positive contribution of educati0n and health to economic growth; the gains from international trade, instead of looking a. it as an instrument of exploitation of the ’periphery’ by the ’centre’; the central role of total factor productivity in achieving high rates of economic growth; and so on.